2022
DOI: 10.1101/2022.07.01.498418
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A conserved role of Hippo signaling in initiation of the first lineage specification event across mammals

Abstract: Our understanding of the molecular events driving cell specification in early mammalian development relies mainly on mouse studies, and it remains unclear whether these mechanisms are conserved across mammals, including humans. We have recently shown that the establishment of cell polarity via aPKC is a conserved event in the initiation of the trophectoderm (TE) placental program in mouse, cow, and human embryos. However, the molecular mechanisms transducing cell polarity into cell fate in cow and human embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 37 publications
7
17
0
Order By: Relevance
“…1cii). Collectively, the expression patterns of these markers indicate that lineage specification does not commence in the compacted guinea pig embryo, aligning with observations in human, rat, and bovine 3 .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…1cii). Collectively, the expression patterns of these markers indicate that lineage specification does not commence in the compacted guinea pig embryo, aligning with observations in human, rat, and bovine 3 .…”
Section: Resultssupporting
confidence: 79%
“…1bii). In contrast, CDX2 emerges in the human, bovine and rat embryo around the time of cavitation 3,21 . Here we see the progressive embryo maturation and distinct expression of CDX2+ emerging in outer cells during the 16C-32C stage, which corresponds to E4.5-E4.75 (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…We confirmed our manual approach by measuring fluorescence intensities of YAP1 and GATA3 at the earlier stages when signals started to emerge, thus when weak signals are more prone to operator error (Fig. 4B) using the 3D Fiji/Image J Suite as previously described (Gerri et al , 2020, 2022).…”
Section: Methodssupporting
confidence: 76%
“…Recent studies have shown that the deactivation of the Hippo signaling pathway is commonly observed in mouse, rat, cow, and human TE. 45,46 Mouse and human trophoblasts share similar epigenetic features. Specifically, tissue-dependent and differentially methylated regions between trophoblast and embryonic lineages are conserved between them.…”
Section: Gene Regulatory Networkmentioning
confidence: 99%
“…Even though there might be species differences at the cellular level, knowledge from mouse experiments help understanding of placental formation in humans. Recent studies have shown that the deactivation of the Hippo signaling pathway is commonly observed in mouse, rat, cow, and human TE 45,46 . Mouse and human trophoblasts share similar epigenetic features.…”
Section: Mouse Placentamentioning
confidence: 99%